Incidence of alcoholism and smoking in medical students - Gómez-Tejeda, Jairo J. (2021)
Introduction: alcohol and smoking are legal drugs most consumed in the world. Many young people have their first contact with these substances between the ages of 12 and 17. Objective: to describe the incidence of alcoholism and smoking in medical students of a Municipal University Center. Holguin-Cuba. Method: s and performed an observational, descriptive, cross - sectional study, whose universe consisted of 73 students, selected through an intentional non - probabilistic sampling, which gave their perpetration reported being worked with the whole. Result: the predominant age was 21 to 23 years and females accounted for the majority of the sample (48). E l 87.6 % and 80.8% consume alcoholic beverages and cigarettes respectively ; the consumption varies from low to medium , predominantly consumption in group 37.5% and 49.1%. The knowledge about the effect of the alcohol (OR: 1.01 p = 0.0002) and smoking (OR 7.7 p = 0.01). The presence of stress was related to alcohol consumption (OR: 4.46 CI: 1.01-18.8 p = 0.03) and smoking (OR: 9.79 CI: 2.61-36.7 p = 0.0001). Conclusions: the consumption of alcohol and cigarettes predominated in low frequency, being more common the ingestion of alcoholic beverages than the habit of smoking and the consumption in groups over the individual. Knowing about the harmful effects of these substances and the presence of stress increased the consumption of alcoholic beverages and cigarettes.